Starship troopers 2 hero of the federation - Tippett, Phil.; Neumeier, Edward; Tri-Star Pictures; Columbia TriStar Home Entertainment (Firm).; Magna Vision (Culver City, Calif. Columbia TriStar Home Entertainment ; distributed in the Philippines by MagnaVision, 2003)
A group of Starship Troopers hide in an abandoned outpost after battling alien bugs. The group recovers, but fails to realize that more danger is ahead.
Director of photography, Christian Sebaldt; production designer, Franco Carbone; editor, Louise Rubacky; music, John Morgan, William Stromberg; costume designer, Jennifer Parsons.
Richard Burgi, Lawrence Monoson, Colleen Porch, Billy Brown, Kelly Carlson, Cy Carter, Sandrine Holt, Ed Lauter J.P. Manoux, Drew Powell, Ed Quinn, Jason-Shane Scott, Brenda Strong.
MPAA rating: R; for violence, sexual content and brief language.
Keywords: Life on other planets -- Drama; Insects -- Drama